Pemanfaatan Teknologi Informasi Dalam Pengelolaan Keuangan UMKM - Amelia Hanna Dana Musdalifah; Susan Rachmawati (Akasia: Artikel Ilmiah Sistem Informasi Akuntansi, 2022)
Abstract - Financial statements are one of the tools that can be used to see the company's performance from one period to another. For this reason, good and correct records are needed and in accordance with generally accepted standards. Zahir accounting is one of the accounting applications that can be used in compiling financial reports more easily and quickly, this is because the language used is Indonesian and the sequence is not much different in preparing financial statements manually. In addition, the advantages of zahir accounting can produce analysis of financial statements and the existence of information that explains the meaning of the numbers contained in the analysis of the resulting financial reports. The research method used is qualitative while the data collection used is interviews, literature studies and literature studies. The results obtained from the research are that UMKMBakmi Kemayoran 21 can compile financial reports more easily, quickly, effectively, efficiently and obtain financial statement analysis to read the company's ability to pay short-term debt, solvency to find out whether it is able to pay off short-term debt with assets that owned while profitability is the company's ability to generate profits. Keywords: Financial Statement Analysis, UMKM